Barriers and facilitators influencing hearing help-seeking behaviors for adults in a peri-urban community in South Africa: a preventive audiology study - Mtimkulu, Thobekile Kutloano; Khoza-Shangase, Katijah; Petrocchi-Bartal, Luisa (Frontiers in Public Health, 2023)
Objective: To examine the barriers and facilitators to accessing ear and hearing care experienced by adults with hearing impairment in a developing South African context. Methods: Twenty-three participants were recruited through purposive sampling from an audiology department of a public hospital in peri-urban South Africa. Individual semi-structured interviews were conducted to capture a broad range of perspectives. Data were analysed through thematic analysis. Results: Socio-economic factors acted as the primary barrier while structural and health system factors were the main facilitator in influencing participants’ journeys towards hearing help-seeking. Conclusion: Numerous factors are at play in help-seeking decisions made by adults with hearing impairment. Individual, provider and environmental factors combine to play a significant role in influencing hearing help-seeking behaviours for adults in a peri-urban community in South Africa. These barriers and facilitators are important to take cognisance of during the planning of preventive audiology initiatives within this context. Plans to implement universal healthcare through the National Health Insurance (NHI) by the South African government must take current findings into consideration to ensure universal access to preventive audiology services.